Polymer rubber article for pet toy and method for processing the same
Patent Information
- Application Number
- CN202611203480.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-10
- Publication Date
- 2026-10-30
AI Technical Summary
当含硫硬橡胶、有机过氧化物、热塑性橡胶和聚酰胺同时处于高温加工环境时,还可能发生多种反应相互竞争,增加加工过程和制品性能的不确定性
[0024]1、本发明采用软质SEBS/SBS基TPR颗粒和高硬度SEBS基TPR颗粒复配形成复合弹性体,软质热塑性橡胶能够赋予制品良好的柔韧性、弹性、回弹性和注塑流动性;高硬度热塑性橡胶中的聚丙烯及硬质苯乙烯链段能够提高材料的承载能力、抗压入能力和抗永久变形能力。通过控制软质热塑性橡胶颗粒与高硬度热塑性橡胶颗粒的质量比,可以避免软质组分过多造成的易咬穿、易撕裂问题,也可以避免高硬度组分过多造成的材料过硬、回弹性降低和注塑流动性变差问题,使制品在柔韧回弹与抗咬破性能之间获得较好的平衡。
Abstract
Description
Technical Field
[0001] This invention relates to the field of rubber materials technology, specifically to a polymer rubber product for pet toys and its processing method. Background Technology
[0002] With the increasing number of pet owners, chew toys that provide functions such as teething, interaction, and energy expenditure for pets have become widely used. These toys are repeatedly subjected to various loads during use, including canine tooth indentation, sharp point puncture, tearing, bending, squeezing, and surface friction, while also being in prolonged contact with pet saliva. Therefore, the materials used in pet chew toys not only need to have appropriate hardness but also need to consider flexibility, resilience, tear resistance, puncture resistance, abrasion resistance, resistance to permanent deformation, and performance stability after being soaked in saliva. For common pet rubber toys, if the hardness is too low, canine teeth can easily form deep indentations on the material surface, further causing perforation or tearing; if the hardness is too high, it will reduce the chewing feel and resilience, and may increase the risk of brittle fracture of the material.
[0003] Current pet chew toys are mainly made of natural rubber, styrene-butadiene rubber (SBR), thermoplastic rubber, thermoplastic elastomers, or ordinary plastics. Natural rubber and SBR possess certain elasticity and abrasion resistance after vulcanization, but their processing typically involves mixing, molding, and vulcanization, resulting in a long production cycle. Vulcanization temperature and time significantly affect product performance, and scraps and waste products are difficult to remelt and process after vulcanization. Thermoplastic rubber can be directly molded using extrusion or injection molding, offering advantages such as high production efficiency, soft touch, and reusability. However, soft thermoplastic rubber has limited resistance to indentation and crack propagation, easily leading to irreversible bite marks, localized deformation, surface tears, or through holes after prolonged chewing by pets.
[0004] To improve the hardness and anti-bite resistance of thermoplastic rubber, existing technologies typically incorporate hard rubber particles, polypropylene, polyamide, or other high-strength resins. Sulfur-containing vulcanized hard rubber has formed an irreversible cross-linked network and cannot be co-melted with thermoplastic rubber. When blended at high temperatures with thermoplastic rubber and polyamide, it easily disperses in the matrix as irregular particles, forming pores or debonding zones at the interface between the soft and hard phases. Under stress, cracks easily originate and propagate from these interfacial defects. Furthermore, differences in shrinkage, viscosity, and thermal history between sulfur-containing hard rubber and thermoplastic rubber can lead to unstable extrusion torque, decreased injection flowability, and uneven local properties in the finished product.
[0005] Polyamides possess high tensile strength, abrasion resistance, and dimensional stability, and their addition to thermoplastic rubbers can improve the material's load-bearing capacity. However, polyamides are polar materials, while styrene-based block copolymer thermoplastic rubbers have relatively low overall polarity, making phase separation prone to occur when the two are directly blended. When the polyamide dispersion is too large or interfacial bonding is insufficient, although the material hardness may increase, the elongation at break and resilience will significantly decrease, and cracks will easily propagate along the interface between the polyamide and elastomer phases. Therefore, simply increasing the amount of polyamide is insufficient to simultaneously improve puncture resistance, tear resistance, and flexibility; the interfacial compatibility between the polyamide and elastomer phases also needs to be addressed.
[0006] On the other hand, the degree of micro-crosslinking in thermoplastic rubber directly affects the material's resilience, resistance to permanent deformation, and melt processing properties. Appropriate micro-crosslinking helps limit irreversible slippage of the elastomer molecular chains, but excessive crosslinking can reduce melt flowability and even form gel particles. If organic peroxides are added during the final blending, granulation, or injection molding stage, the decomposition of the peroxides in the high-temperature barrel may cause further crosslinking or chain breakage in the elastomer, resulting in changes in material viscosity and flowability with residence time. When sulfur-containing hard rubber, organic peroxides, thermoplastic rubber, and polyamide are simultaneously in a high-temperature processing environment, multiple competing reactions may occur, increasing the uncertainty of the processing and product performance. Summary of the Invention
[0007] The purpose of this invention is to provide a polymer rubber product for pet toys and a processing method thereof, so as to solve the problems existing in the prior art.
[0008] To solve the above-mentioned technical problems, the present invention provides the following technical solution: a polymer rubber product for pet toys, comprising 65-80 parts by weight of a composite elastomer, 20-35 parts by weight of special nylon PA12, 6-10 parts by weight of SEBS-g-MAH, 8-15 parts by weight of composite modified wollastonite, 0.3-0.8 parts by weight of antioxidant, and 0.5-1.2 parts by weight of lubricant; wherein the composite elastomer is composed of soft SEBS / SBS-based TPR particles and high-hardness SEBS-based TPR particles in a mass ratio of 60-75:25-40.
[0009] Furthermore, the composite elastomer is preferably 70 parts by weight, and the special nylon is preferably 30 parts by weight.
[0010] This invention incorporates a special type of nylon as a high-strength reinforcing phase dispersed in a composite rubber system. This improves the material's tensile strength, puncture resistance, abrasion resistance, and dimensional stability, while reducing the risk of permanent deformation caused by prolonged chewing by pets. The special nylon possesses high strength and abrasion resistance, forming a supporting skeleton within the rubber's elastic phase. This prevents the product from being punctured, torn, or collapsed when subjected to sharp-tooth compression, tearing, or repeated bending.
[0011] Furthermore, the composite modified wollastonite is composed of component A and component B. Component A is large-particle-size wollastonite modified with coupling agent KH560 and then epoxy ring-grafted with carboxymethyl chitosan. Component B is small-particle-size wollastonite modified with allyltrimethoxysilane. The mass ratio of component A to component B is 1.2-2.5:1.
[0012] Furthermore, the SEBS-g-MAH has a number-average molecular weight Mn of 100,000-130,000, a styrene content of 25%-30%, and a maleic anhydride grafting rate of 1.0%-1.5%.
[0013] Furthermore, the SEBS has a number-average molecular weight Mn of 100,000-150,000 and a styrene content of 18%-25%.
[0014] Furthermore, the SBS is linear SBS with a number-average molecular weight Mn of 90,000-120,000 and an S / B mass ratio of 30:70-35:65.
[0015] Furthermore, component B is added during the melt pre-forming stage of soft SEBS / SBS-based TPR.
[0016] Furthermore, the large-particle-size wollastonite has a D50 of 12-25 μm and an aspect ratio of 10:1-20:1.
[0017] Furthermore, the small-particle-size wollastonite has a D50 of 1-4 μm and an aspect ratio of 3:1-8:1.
[0018] Furthermore, the soft SEBS / SBS-based TPR comprises, by weight parts, 60-80 parts SEBS, 35-50 parts SBS, 45-65 parts food-grade white oil, 4-8 parts SEBS-g-MAH, 0.10-0.25 parts dicumyl peroxide, 0.20-0.50 parts triallyl isocyanurate, 0.3-0.8 parts antioxidant, and 0.3-1.0 parts lubricant.
[0019] Furthermore, the high-hardness SEBS-based TPR comprises, by weight parts, 60-80 parts SEBS, 10-25 parts SBS, 15-25 parts polypropylene, 5-15 parts food-grade white oil, 0.3-0.8 parts antioxidant, and 0.3-1.0 parts lubricant.
[0020] Furthermore, the antioxidant is composed of antioxidant 1010 and antioxidant 168 in a mass ratio of 1-3:1-3.
[0021] This invention also provides a method for preparing polymer rubber products for pet toys, comprising the following steps: preparing component A and component B separately; mixing component B with SEBS, SBS, food-grade white oil, SEBS-g-MAH, dicumyl peroxide, triallyl isocyanurate, antioxidant and lubricant, melting and mixing at 165-175℃ for 60-120s and then pelletizing to obtain soft TPR granules containing component B; mixing the soft TPR granules with high-hardness SEBS-based TPR granules to obtain a composite elastomer; adding the composite elastomer, PA12 and SEBS-g-MAH from the main feed port of a twin-screw extruder, and feeding component A from the middle and rear sections after the material melts, extruding, cooling and pelletizing, and injection molding at a barrel temperature of 195-202℃ and a mold temperature of 40-60℃.
[0022] This invention, through synergistic modification with KH560 and allylsilane, improves the dispersion stability of chitosan in SEBS / SBS elastomer and nylon phases. After chitosan is fixed on the wollastonite surface, it can further agglomerate and concentrate stress, thereby improving the puncture resistance, tear resistance, abrasion resistance, and wet mechanical properties of the product. Simultaneously, considering that chitosan may undergo dehydration, chain breakage, or thermal oxidative degradation at higher melt processing temperatures, this invention adds chitosan-modified wollastonite via side feeding during the later stages of extrusion. Preferably, the side feeding zone temperature is controlled at 185-195℃, the injection molding front section and nozzle temperature at 202-208℃, and the material residence time in the high-temperature zone does not exceed 3-5 minutes to reduce the adverse effects of chitosan chain thermal degradation on interface regulation.
[0023] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0024] 1. This invention uses a composite elastomer formed by blending soft SEBS / SBS-based TPR particles and high-hardness SEBS-based TPR particles. The soft thermoplastic rubber imparts good flexibility, elasticity, resilience, and injection molding flowability to the product; the polypropylene and rigid styrene segments in the high-hardness thermoplastic rubber improve the material's load-bearing capacity, indentation resistance, and resistance to permanent deformation. By controlling the mass ratio of soft thermoplastic rubber particles to high-hardness thermoplastic rubber particles, the problems of easy biting and tearing caused by excessive soft components can be avoided, as well as the problems of excessive hardness, reduced resilience, and poor injection molding flowability caused by excessive high-hardness components. This achieves a good balance between flexibility, resilience, and anti-biting performance in the product.
[0025] 2. This invention utilizes the skeletal load-bearing effect of large-diameter wollastonite and the interstitial filling effect of small-diameter wollastonite to make the packing and distribution of fillers in the composite material more uniform, which is beneficial to simultaneously improving the material's puncture resistance, tear resistance and wear resistance. Detailed Implementation
[0026] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0027] Example 1
[0028] (1) Take 100 parts by weight of large-particle needle-shaped wollastonite with D50 of 15 μm and aspect ratio of 12:1, add it to 700 parts by weight of deionized water, adjust the pH to 4.5 with dilute acetic acid, sonicate at 600W for 8 min, stir at 400 rpm for 30 min, filter, wash with water until the pH of the filtrate is 6.5-7.5, dry at 80℃ for 4 h to obtain activated large-particle wollastonite;
[0029] (2) 2.5 parts by mass of KH560 were added to a mixed solvent consisting of 320 parts by mass of ethanol and 80 parts by mass of deionized water. The pH was adjusted to 4.5 with acetic acid and pre-hydrolyzed at 25°C and 300 rpm for 30 min. 100 parts by mass of activated large-particle wollastonite were added and reacted at 60°C and 500 rpm for 3 h. After filtration, the mixture was washed twice with ethanol and once with deionized water. It was then vacuum dried at 70°C for 4 h to obtain epoxy silane modified large-particle wollastonite.
[0030] (3) Prepare a 2% aqueous solution of 6 parts by mass of water-soluble carboxymethyl chitosan with a degree of deacetylation of 85%, a degree of carboxymethyl substitution of 0.75, and a number-average molecular weight of 100,000. Adjust the pH to 8.2 with sodium bicarbonate. Add 0.05 parts by mass of triethylamine, which is 2% of the mass of KH560. Add 100 parts by mass of epoxy silane-modified large-particle wollastonite. React at 60°C and 300 rpm for 6 h. After the reaction is complete, filter the solution and wash it with deionized water until the pH of the filtrate is 6.5-7.5. Wash it once with ethanol and dry it under vacuum at 50°C for 6 h to obtain component A.
[0031] (4) 1.5 parts by mass of allyltrimethoxysilane were added to a mixed solvent consisting of 360 parts by mass of ethanol and 40 parts by mass of deionized water, the pH was adjusted to 4.5, and pre-hydrolyzed at 25°C for 30 min; 100 parts by mass of small-particle-size wollastonite with a D50 of 1.5 μm and an aspect ratio of 4:1 were added, and the mixture was reacted at 60°C and 600 rpm for 3 h. The mixture was filtered, washed twice with ethanol and once with deionized water, and then vacuum dried at 80°C for 4 h to obtain component B.
[0032] (5) Take 70 parts by weight of SEBS, 40 parts by weight of SBS, 55 parts by weight of food-grade white oil, 5 parts by weight of SEBS-g-MAH, 0.25 parts by weight of antioxidant 1010, 0.25 parts by weight of antioxidant 168 and 0.8 parts by weight of zinc stearate. Premix SEBS, SBS and white oil at 50°C for 45 min. Then add 4 parts by weight of component B, 0.15 parts by weight of dicumyl peroxide and 0.25 parts by weight of triallyl isocyanurate. Mix using a twin-screw extruder with the following temperatures: Zone 1 120°C, Zone 2 145°C, Zone 3 165°C, Zone 4 170°C, Zone 5 170°C, and die head 168°C. The screw speed is 180 rpm. The material stays in the zone above 165°C for 75 s. Extrude and pelletize to obtain micro-crosslinked soft TPR particles.
[0033] (6) Take 70 parts by weight of SEBS, 15 parts by weight of SBS, 20 parts by weight of polypropylene, 10 parts by weight of food-grade white oil, 0.25 parts by weight of antioxidant 1010, 0.25 parts by weight of antioxidant 168 and 0.5 parts by weight of zinc stearate, mix them and extrude and pelletize them at 160-180℃ to obtain high hardness SEBS-based TPR particles;
[0034] (7) Mix micro-crosslinked soft TPR particles and high-hardness SEBS-based TPR particles in a high-speed mixer at a mass ratio of 70:30 at 800 rpm for 5 min, with the mixing temperature not exceeding 60℃, to obtain a composite elastomer.
[0035] (8) Take 75 parts by weight of composite elastomer, 25 parts by weight of PA12 and 6 parts by weight of SEBS-g-MAH and add them into the main feed port of the twin-screw extruder; the temperatures of each zone of the extruder are 150℃, 170℃, 185℃, 195℃, 190℃ and 185℃ respectively, and the screw speed is 220 rpm. After the material has completely melted, feed 6 parts by weight of component A from the side of the fifth zone. Control the residence time of component A after entering the melt to be 60-90s. The material is extruded, water-cooled, air-dried and pelletized to obtain composite particles.
[0036] (9) The composite granules were dehumidified and dried at 80℃ for 4 hours to ensure a moisture content of no more than 0.10%. The temperatures of the rear, middle, and front sections of the injection molding machine barrel and the nozzle were 180℃, 190℃, 198℃, and 198℃, respectively. The mold temperature was 45℃, the injection pressure was 65MPa, the holding pressure was 35MPa, the holding time was 10s, and the cooling time was 30s. After the product cooled and solidified, it was demolded and trimmed.
[0037] Examples 2-6
[0038] Examples 2-6 were prepared in the same order as Example 1, and the main formulations of each example are shown in Table 1. Solvent ratios, washing methods, soft TPR base resin composition, high-hardness TPR composition, and final side-feeding methods not listed are the same as in Example 1.
[0039] Table 1 Formulation of Examples
[0040] Composite elastomer / part 75 65 70 72 78 68 PA12 / serving 25 35 30 28 22 32 Soft TPR: High-hardness TPR 70:30 60:40 65:35 62:38 75:25 68:32 SEBS-g-MAH / serving 6 10 8 7 6 9 Component A / parts 6 9 7 8 5 8 Component B / part 4 4 4 5 4 4 Large / small particle size D50 / μm 15 / 1.5 25 / 4 18 / 2 20 / 3 12 / 1 22 / 3 KH560 / Large-diameter wollastonite / % 2.5 4.0 3.0 3.5 2.0 3.0 Carboxymethyl chitosan / % 6 15 8 10 5 12 Triethylamine / KH560 / % 2 5 3 4 1 3 Allylsilane / % 1.5 3.0 2.0 2.5 1.0 2.0 dicumyl peroxide / part 0.15 0.25 0.2 0.22 0.1 0.2
[0041] Comparative Example 1
[0042] The difference between Comparative Example 1 and Example 3 is that neither the large nor small particle size wollastonite is modified, while the rest of the preparation methods are the same as in Example 3.
[0043] Comparative Example 2
[0044] The difference between Comparative Example 2 and Example 3 is that component B is not added, and the amount of component A is adjusted to 11 parts. The rest of the preparation method is the same as in Example 3.
[0045] Comparative Example 3
[0046] The difference between Comparative Example 3 and Example 3 is that component A is not added, and the amount of component B is adjusted to 11 parts. The rest of the preparation method is the same as in Example 3.
[0047] Comparative Example 4
[0048] The difference between Comparative Example 4 and Example 3 is that no composite modified wollastonite is added, while the rest of the preparation methods are the same as in Example 3.
[0049] Comparative Example 5
[0050] The difference between Comparative Example 5 and Example 3 is that high-hardness SEBS-based TPR particles are not added, while the rest of the preparation methods are the same as in Example 3.
[0051] Comparative Example 6
[0052] The difference between Comparative Example 6 and Example 3 is that the ratio of micro-crosslinked soft TPR particles to high-hardness SEBS-based TPR particles is 65:35, while the rest of the preparation method is the same as in Example 3.
[0053] Comparative Example 7
[0054] The difference between Comparative Example 7 and Example 3 is that no special nylon is added, while the rest of the preparation method is the same as in Example 3.
[0055] Performance testing
[0056] Puncture resistance: 50mm diameter, 2.0±0.1mm thick circular specimens were clamped between ring clamps with an inner diameter of 20mm. A 3.0mm diameter, 1.5mm end radius hemispherical stainless steel probe was vertically pressed into the center of the specimen at a speed of 50mm / min. The maximum force before complete penetration was recorded. Five specimens were tested in each group, and the average value was taken.
[0057] Table 1
[0058] GB / T531.1-2008 GB / T528-2009 GB / T528-2009 GB / T529-2008 Right Angle Method GB / T7759.1-2015(25%,70℃×22h) GB / T 1681-2009 Dropped Ball 40℃×7d Artificial saliva Example 1 58 16.5 420 64 27.0 58 122 92 Example 2 76 22.8 285 84 18.5 46 181 95 Example 3 68 22.0 350 82 19.2 53 168 96 Example 4 71 21.4 330 79 20.0 51 159 95 Example 5 55 15.8 450 60 28.5 61 106 91 Example 6 73 22.2 315 81 19.0 49 172 94 Comparative Example 1 66 14.6 260 53 32.5 43 88 84 Comparative Example 2 70 15.2 270 57 30.8 44 101 89 Comparative Example 3 63 14.8 275 54 31.5 45 92 87 Comparative Example 4 58 12.9 250 47 35 41 72 80 Comparative Example 5 52 12.5 265 45 38 42 68 82 Comparative Example 6 89 20.4 300 77 20.9 49 99 85 Comparative Example 7 82 17.2 430 55.8 28.5 60 62 76
[0059] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from its spirit or essential characteristics. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, all variations falling within the meaning and scope of equivalents of the claims are intended to be included within the present invention. No markings in the claims should be construed as limiting the scope of the claims.
Claims
1. A polymer rubber product for pet toys, characterized in that, It comprises 65-80 parts by weight of composite elastomer, 20-35 parts by weight of special nylon PA12, 6-10 parts by weight of SEBS-g-MAH, 8-15 parts by weight of composite modified wollastonite, 0.3-0.8 parts by weight of antioxidant, and 0.5-1.2 parts by weight of lubricant; the composite elastomer is composed of soft SEBS / SBS-based TPR particles and high-hardness SEBS-based TPR particles in a mass ratio of 60-75:25-40.
2. The polymer rubber product for pet toys according to claim 1, characterized in that, The composite modified wollastonite consists of component A and component B. Component A is large-particle-size wollastonite modified with coupling agent KH560 and then epoxy ring-grafted with carboxymethyl chitosan. Component B is small-particle-size wollastonite modified with allyltrimethoxysilane. The mass ratio of component A to component B is 1.2-2.5:
1.
3. A polymer rubber product for pet toys according to claim 2, characterized in that, Component B is added during the melt pre-fabrication stage of soft SEBS / SBS-based TPR.
4. A as described in claim 2, characterized in that, According to claim 2, the polymer rubber product for pet toys is characterized in that the large-particle-size wollastonite has a D50 of 12-25 μm and an aspect ratio of 10:1-20:
1.
5. A polymer rubber product for pet toys according to claim 2, characterized in that, The small-particle-size wollastonite has a D50 of 1-4 μm and an aspect ratio of 3:1-8:
1.
6. A polymer rubber product for pet toys according to claim 1, characterized in that, The soft SEBS / SBS-based TPR comprises, by weight parts, 60-80 parts SEBS, 35-50 parts SBS, 45-65 parts food-grade white oil, 4-8 parts SEBS-g-MAH, 0.10-0.25 parts dicumyl peroxide, 0.20-0.50 parts triallyl isocyanurate, 0.3-0.8 parts antioxidant, and 0.3-1.0 parts lubricant.
7. A polymer rubber product for pet toys according to claim 1, characterized in that, The high-hardness SEBS-based TPR comprises, by weight parts, 60-80 parts SEBS, 10-25 parts SBS, 15-25 parts polypropylene, 5-15 parts food-grade white oil, 0.3-0.8 parts antioxidant, and 0.3-1.0 parts lubricant.
8. A method for preparing a polymeric rubber product for pet toys according to any one of claims 1-7, characterized in that, Includes the following steps: Component A and Component B are prepared separately. Component B is mixed with SEBS, SBS, food-grade white oil, SEBS-g-MAH, dicumyl peroxide, triallyl isocyanurate, antioxidant, and lubricant. After melt mixing at 165-175℃ for 60-120s, the mixture is pelletized to obtain soft TPR granules containing Component B. The soft TPR granules are mixed with high-hardness SEBS-based TPR granules to obtain a composite elastomer. The composite elastomer, PA12, and SEBS-g-MAH are added from the main feed port of a twin-screw extruder. After the material melts, Component A is fed from the middle and rear sections. The extrusion is carried out, cooled, and pelletized. Injection molding is performed at a maximum barrel temperature of 195-202℃ and a mold temperature of 40-60℃.
